'PROTESTANTISM' AS A HISTORICAL CATEGORY. (29th September 2016) - Ryrie, Alec
ABSTRACT: The term 'Protestant' itself is a historical accident, but the category of western Christians who have separated from Rome since 1517 remains a useful one. The confessionalisation thesis, which has dominated recent Reformation historiography, instead posits the two major Protestant confessions and Tridentine Catholicism as its categories, but this can produce a false parallelism in which the nature of the relationship between the confessions is oversimplified. Instead, this paper proposes we think of a Protestant ecosystem consisting of self-consciously confessional Lutheranism, a broad Calvinism which imagined itself as normative, and a collection of radical currents much more intimately connected to the 'magisterial' confessions than any of the participants wished to acknowledge. The magisterial / radical division was maintained only with constant vigilance and exemplary violence, with Calvinism in particular constantly threatening to bleed into radicalism. What gives this quarrelsome family of 'Protestants' analytical coherence is neither simple genealogy nor, as has been suggested, mere adherence to the Bible: since in practice both 'radical' and 'magisterial' Protestants have been more flexible and 'spiritual' in their use of Scripture than is generally allowed. It is, rather, the devotional experience underpinning that 'spiritual' use of the Bible, of an unmediated encounter with grace.